Guidelines for next-generation sequencing in sarcoma diagnosis and treatment: a consensus review - Serrano, César; Bauer, Sebastian; Blay, Jean-Yves; Casali, Paolo G.; Cicala, Carlo M.; Dei Tos, Angelo P.; Digklia, Antonia; Gelderblom, Hans; Italiano, Antoine; Jones, Robin L.; Kasper, Bernd; Kyriazoglou, Anastasios; et al. (JAMA oncology, 2025)
Sarcomas comprise a heterogeneous group of malignant neoplasms that include genomically simple (driven by recurrent genetic alterations) and genomically complex (characterized by extensive genomic rearrangements) subtypes. Regardless, sarcomas exhibit a remarkably low mutational burden. In this context, there is a growing demand for the use of next-generation sequencing (NGS)−based technologies to aid in the clinical management of patients with sarcoma. However, a broad, clinically impactful implementation faces inherent challenges associated with their rarity, heterogeneity, and limited molecular understanding.From a diagnostic standpoint, there is a lack of prospective studies comparing up-front, indiscriminate use of NGS fusion panels in all new cases suggestive of sarcoma diagnosis in comparison with a use only indicated by a sarcoma-expert pathologist during the assessment. Therefore, although a significant proportion of sarcomas harbor specific molecular alterations, not all cases require NGS for a definitive diagnosis given that most sarcoma subtypes display classic histologic features. From a therapeutic perspective, current evidence does not support routine clinical use of NGS in all patients with sarcoma due to the small number of actionable alterations and the limited evidence for clinical benefit achieved with NGS-matched treatments. Although certain entities and molecular backgrounds demonstrate potential advantages, the consensus group emphasizes that indication of targeted agents for treatment is largely based on the specific subtype, and therefore, an accurate diagnosis is indispensable.Evidence supporting the routine, nonselective use of NGS in patients with sarcoma is currently limited. Given the complexity, the decision to perform an NGS panel, as well as the interpretation and use of its results for diagnostic or therapeutic purposes, should take place only in sarcoma-expert institutions, including a multidisciplinary review. The results of multigene panels performed in nonexpert sarcoma centers cannot replace the pathology review or the recommendation of NGS-guided therapies without prior evaluation by sarcoma experts.
Gesehen am 27.11.2025